An evaluation of the hot-hand hypothesis in the NBA when accounting for shot difficulty - Kondur, A.; Shen, W. (International Journal of Sports Science & Coaching, 2025)
The hot-hand hypothesis suggests that athletes can experience periods of exceptional performance where the success of their next action is influenced by previous successes. This study examines the hot-hand phenomenon in the context of the NBA, focusing on shot difficulty as a critical factor. Previous research has yielded conflicting results, often ignoring the varying difficulty of shots and the role of defensive pressure. Utilizing shot log data from the 2014-2015 NBA season, this paper introduces new models that account for shot difficulty with defender proximity. By employing XGBoost classifiers and difficulty-weighted metrics, we find that while traditional hot-hand effects are minimal, adjusting for shot difficulty reveals a reverse hot-hand effect: players tend to perform worse following streaks of successful but difficult shots. This research provides a nuanced understanding of the hot-hand phenomenon, highlighting the importance of considering shot difficulty in sports performance analysis. These findings have implications for coaching strategies and the psychological interpretation of performance streaks in competitive basketball.